Meningkatkan Literasi Anak Jalanan Melalui Taman Baca - Randa Gempa Saputra; Solfema Solfema; Lili Dasa Putri (BADAN PENERBIT STIEPARI PRESS, 2025)
One way to improve the welfare of street children through informal education is to build reading parks. This article discusses the function of reading parks in providing opportunities to learn something, prepare skills, and reveal the potential of street children, who often cannot access formal education. In addition to creating children with complex reading mechanisms, a place for play, and learning, they also provide a reduction in the risk of children usually engaging in risky activities such as child exploitation and crime. Apart from discussing the benefits, this article also explores the impact of reading gardens on children's self-concept, emotions and relationships as readers. Finally, the discussion concludes with the emphasis that reading gardens may be a necessary step to contend with superficial poverty and the long-term well-being of street children. This research was carried out by collecting data from previously existing journals, papers and articles, starting from a sense of concern for the educational needs of street children which are often neglected. The results of this research show that reading parks are not only a means of learning, but also provide hope and opportunities for street children to access inclusive education.